2012
DOI: 10.1111/j.1744-313x.2012.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of interleukin‐8, CXCR1 and CXCR2 genes and risk of acute pyelonephritis in children

Abstract: Acute pyelonephritis (APN) is the most severe form of urinary tract infection, the etiopathogenesis of which is still not well understood. Previous studies demonstrated that chemotaxis of neutrophils into the tissue and across the infected epithelial layer is a key step in rapid bacterial clearance. Variations within genes encoding the major chemokine interleukin-8 and its receptors CXCR1 and CXCR2 are therefore attractive candidates for participation in genetic predisposition to APN. The aim of our study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The mutant CXCR1-T276 SNP, which has been associated with increased susceptibility to bacterial renal infection in two independent cohorts of pediatric patients (14,15), provided a unique translational opportunity to extend our mouse findings to humans. Hence, we found that the CXCR1-T276 allele is associated with an increased likelihood for the development of disseminated candidiasis in candidemic patients of mixed European descent.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant CXCR1-T276 SNP, which has been associated with increased susceptibility to bacterial renal infection in two independent cohorts of pediatric patients (14,15), provided a unique translational opportunity to extend our mouse findings to humans. Hence, we found that the CXCR1-T276 allele is associated with an increased likelihood for the development of disseminated candidiasis in candidemic patients of mixed European descent.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study involving breast cancer patients with invasive ductal carcinoma, the CXCR2 +1208 C/T polymorphism showed no differences between studied groups (Kamali-Sarvestani et al, 2007). In a study conducted in Slovakia, the CXCR2 +1208 T allele was the least represented in that community and conferred protection from recurrent acute pyelonephritis (APN), which is the most severe form of urinary tract infection (Javor et al, 2012). Because of the limited number of participants in our study, further studies are necessary to confirm these results.…”
Section: Discussionmentioning
confidence: 40%
“…Two hundred and eighty‐four publications were retrieved from electronic databases. Eight studies met our inclusion and exclusion criteria, of which seven reported CXCR1 rs2234671 and two reported CXCR1 rs3138060 . Detailed genetic frequencies of CXCR1 rs16858808, CXCR2 1126579, and rs4674258 were reported in one article each (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, Gond et al did not find any association between CXCR1 rs2234671 polymorphism and UTI susceptibility in adults, whereas Yin et al reported that rs2234671 GC genotype and C allele have lower prevalence in UTI sufferers than in controls . These paradoxical results were also observed in children …”
mentioning
confidence: 98%